Islamic Economic Law in the Digital Age: Navigating Global Challenges and Legal Adaptations - Asyiqin, Istianah Zainal (Media Iuris, 2025)
This study examines the challenges and adaptations of Islamic economic law in addressing global economic transformations in the digital era, particularly in Indonesia. The research aims to analyze how Islamic legal frameworks respond to the rise of fintech, blockchain, and smart contracts while maintaining compliance with Sharia principles. Employing a qualitative approach with doctrinal legal research, this study utilizes primary legal sources such as the Quran, Sunnah, Ijma’, and Qiyas, along with national regulations, including the Sharia Banking Law, Financial Services Authority (OJK) regulations, and fatwas from the Indonesian Ulema Council (MUI). Data are collected through legal document analysis and case studies on the implementation of Islamic finance in digital transactions. The findings indicate that while Indonesia has made significant progress in integrating Sharia-compliant financial technologies, challenges remain in ensuring regulatory clarity, consumer protection, and the prevention of Sharia non-compliance risks. The study concludes that continuous legal adaptation and regulatory innovation are essential to uphold Islamic economic principles in the evolving global digital economy.